Management of tympanic retraction pockets: case of Mali - Konaté, N’faly; Diarra, Kassim; Dembelé, Yaya; Dao, Adama; Elmehdi Elansari, Mohamed Saydi Ag Med; Traoré, Youssouf; Sanogo, Harouna; Bagayoko, Drissa Kaloga; Sidibé, Youssouf; Soumaoro, Siaka; Guido, Boubacary; Issa Koné, Fatogoma; et al. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Background: This study aims to study the epidemiological and therapeutic aspects of tympanic retraction pockets in the ENT-CCF department of the CHU GT. Method: This was a descriptive prospective study. Results: A total of 9400 patients consulted during the study period. A retraction pocket was diagnosed in 70 patients, i.e., 0.74% of all consultations. The most represented age group was that of [25-39 years]. The average age was 45.71 years. The extremes of ages were 10 years and 81 years. The female gender was the most represented, i.e., 60% with a sex ratio꞊0.67. CT of the petrous bone was performed in two patients. Medical treatment based on systemic corticosteroids and nasal decongestant was initiated in all our patients associated with quarterly monitoring for stage I charachon. The placement of a tympanostomy tube was performed in 8 patients classified (stage II of charachon). Cartilaginous tympanoplasty was performed in one patient, antroatticotomy associated with reinforcement tympanoplasty was performed in one patient (1.43%). Conclusions: The pockets of tympanic retraction constitute a particular nosological entity which deserves rigorous monitoring. The ENT surgeon will be faced with two major challenges: the erosion of the ossicular chain and their potential risk of progression towards cholesteatoma. The diversity of therapeutic options represents an issue that makes this entity a hot topic.